Silicon application enhances resistance to xanthomonas wilt disease in banana - Mburu, K.; Oduor, R.; Mgutu, A.J.; Tripathi, L. (Wiley, 2016)
Silicon (Si) has been reported to be a beneficial element and shown to enhance disease resistance in many crops, although it is not regarded to be critical for plant growth and development. In this study, the potential effect of Si supplementation on resistance to banana xanthomonas wilt (BXW) disease was evaluated using various banana cultivars. Si application at a concentration of 200 mg per plant per week was found to be optimal in enhancing resistance to BXW without any detrimental effects on plant growth. The effect of varying the duration of Si application showed continuous supply of Si before and after pathogen inoculation led to a significantly higher level of resistance to BXW in all the banana cultivars tested in comparison to non-Si-treated inoculated plants. Banana plants treated with Si before pathogen inoculation only, also exhibited high protection against BXW similar to plants treated continuously with Si. The total Si content in leaves increased significantly in Si-treated plants in comparison to non-Si-treated control plants. The amount of Si accumulation was directly correlated to the duration of application; plants treated with Si continuously showed significantly higher amounts of Si accumulation in leaves than plants where Si application was terminated following bacterial inoculation or when Si application started immediately after pathogen inoculation. The Si-treated plants also showed higher activity of the peroxidase enzyme in comparison to non-Si-treated control plants. This study confirms that application of Si enhances resistance to BXW and may provide an alternative disease management strategy.